Examination of Macular Retina and Choroidal Thickness in High Myopic Amblyopia Using Spectral-Domain Optical Coherence Tomography - Wan, Juan; Zhang, Zhengwei; Tian, Yu (Frontiers in Medicine, 2022)
Purpose: The aim of this study was to investigate changes in the retinal and choroidal thickness between high myopic amblyopia (HMA), low myopia (LM), moderate myopia (MM), high myopia (HM), and healthy children (NG) using a spectral-domain optical coherence tomography (SD-OCT). Materials and Methods: A total of 75 Chinese children (128 eyes; mean age 10.5 years old) were recruited. Retinal thickness (RT) and choroidal thickness (CT) was measured at different locations (subfoveal (SF), 0.5mm/1.0mm/1.5mm/2.0mm/2.5mm/3.0mm to the fovea in superior, nasal, inferior and temporal sector) using enhanced depth imaging (EDI) system of SD-OCT. Axial length (AL), best-corrected visual acuity (BCVA), and refraction errors were also collected. Results: No significant differences were found in subfoveal retinal thickens (SFRT). Moreover, a significantly thinner subfoveal choroidal thickness (SFCT) was found in HMA compared to NG, LM, MM patients; but not compared to HM group. At retinal thickness (RT) of 0.5mm to fovea, HMA was significantly thinner compared to LM and MM in the three sectors (superior, inferior and temporal); nevertheless, no significant differences were found compared to NG and HM group. For choroidal thickness (CT) at 0.5mm to fovea, HMA was significantly thinner in all four sectors compared to other three groups, except for HM group. For RT at 1.0mm/1.5mm/2.0mm/2.5mm/3.0mm to fovea, HMA was thinner compared to NG, LM and MM group. For CT at 1.0mm/1.5mm/2.0mm/2.5mm/3.0mm to fovea, HMA was thinner compared to NG, LM, and MM group; while for superior and inferior sectors, HMA showed to be statistically thinner compared with HM group. Moreover, SFCT in the HMA, HM and NG were negatively correlated with AL. Conclusions: Thinner retinal and choroidal tissue appear to be related to HMA, and thus can be used as a useful parameters for discovering the underlying mechanisms of the disease.